Is Sub-Saharan Africa Catching Up? - Noguera-Santaella, J (Springer Verlag, 2017)
This paper examines the catching-up process of sub-Saharan African countries. For that purpose, it investigates whether sub-Saharan African countries have shown a change in trend in their per capita GDP and whether these countries are closing the gap with developed economies, taking as reference the long-run per capita income growth rate of the USA. To test for changes in the level or in the trend, we use the algorithm developed by Kejriwal and Perron (J Time Ser Anal 31:305–328, 2010. doi:10.1111/j.1467-9892.2010.00666.x) to detect structural breaks for each sub-Saharan African country for the period 1950–2010 and then verify whether per capita income paths eventually converge to their long-run trend. We find evidence that some countries have been doing well since their independence. They include Botswana, Equatorial Guinea, Ghana, Lesotho, Mauritius, Rwanda and Seychelles. After having a poor performance, we also find that some others have changed their luck and have started a catching up process. They include Angola, Cape Verde, Eritrea–Ethiopia, Mauritania, Mozambique, Sierra Leone, Sudan, Tanzania and Uganda. All other are still falling behind. © 2016, Springer-Verlag Berlin Heidelberg.